The relational–functional foundation of public relations as a tool for building the corporate image - Imene, Khalfa (The International tax journal, 2025)
This research examines the mechanism of public relations as a function that contributes to the construction of the corporate image and the consolidation of the institution's standing among its various publics. Its role is no longer confined to the transmission of information or the management of communication; instead, it has become a strategic activity based on establishing an integrated system of functional relationships through which trust and credibility are reinforced. This foundation is grounded in the principle that the corporate image is shaped through continuous, balanced interaction between the institution and its communicative environment, which necessitates adopting modern approaches that focus on relationship management rather than merely on message management. Within this framework, public relations works to develop a network of reciprocal links through planning, research, and two-way communication mechanisms, thereby enabling the creation of mutual understanding of the institution’s identity, values, and performance. This relational dynamic constitutes the cornerstone of contemporary public relations functions, particularly in light of developments occurring within competitive environments characterised by digital transformation and heightened public sensitivity towards organisational conduct.